Growth Response of Mung Bean Plants Vigna radiata L. and Spinach Amaranthus hybridus L. Under Acidic and Alkaline Conditions - Ramadhan, Dwi Sapri; Wardana, Dian; Fahmi, Jaman; Safitri, Wulan Dwi; Lubis, Ghania Dhia Ulhaq; Nainggolan, Lidya Revalina; Zubir, Moondra; Siregar, Nurdin (Universitas Negeri Medan, 2025)
This study investigates the growth response of mung bean Vigna radiata L. and spinach Amaranthus hybridus L. under controlled acidic neutral and alkaline environments across a wide pH gradient from pH 3 to pH 14. The work provides a comparative assessment of two species with distinct physiological characteristics to clarify how hydrogen ion concentration shapes vegetative development. The novelty of this study lies in its direct evaluation of extreme pH conditions using a uniform experimental design that allows both species to be examined under identical chemical exposure, enabling a clear contrast of tolerance thresholds. Plant height was recorded daily for 13 days to capture early stage vegetative dynamics. Both species exhibited their highest stability near pH 7 while severe deviations from neutrality reduced growth through nutrient imbalance and physiological stress. Mung bean showed moderate tolerance at pH 9.5 whereas spinach displayed enhanced performance within mild alkalinity. Strong acidity and strong alkalinity produced structural damage in both species. The findings highlight the critical role of soil pH in plant performance and provide foundational insight into species specific tolerance ranges that can support more informed management of crops grown in chemically variable environments.